2020
DOI: 10.1097/inf.0000000000002976
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Early and Late Onset Neonatal Sepsis in Very Low Birthweight Infants

Abstract: Background: Sepsis is a major cause of death in neonates. Knowledge about epidemiology, risk factors, causative pathogens and outcome of neonatal sepsis is important to improve neonatal care. For Germany, only few data on neonatal sepsis in very low birth weight (VLBW) infants exist. Methods: Data from 14,926 preterm infants with birth weight <1500 g and gestational age between 22 0/7 weeks and 31 6/7 collected between January 2009 and December 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 30 publications
3
36
2
Order By: Relevance
“…This is in line with data from Germany and the USA, reporting that more than 80% of VLBWI receive early antibiotics [ 4 , 16 ]. Incidence of sepsis during the first week (EOS and LOS) was low in our cohort (4.8% for infants < 32 weeks) according to data from Germany [ 1 ] and other countries [ 17 , 18 ]). In 28.1% of infants receiving antibiotics in the first postnatal week, therapy was terminated within 48 h, suggesting clinical resolution of symptoms and no increase in inflammation markers.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This is in line with data from Germany and the USA, reporting that more than 80% of VLBWI receive early antibiotics [ 4 , 16 ]. Incidence of sepsis during the first week (EOS and LOS) was low in our cohort (4.8% for infants < 32 weeks) according to data from Germany [ 1 ] and other countries [ 17 , 18 ]). In 28.1% of infants receiving antibiotics in the first postnatal week, therapy was terminated within 48 h, suggesting clinical resolution of symptoms and no increase in inflammation markers.…”
Section: Discussionmentioning
confidence: 83%
“…Although neonatal sepsis with Enterobacter spp . is comparatively rare [ 1 , 23 ], it has been shown that a high relative abundance of Enterobacter cloacae is associated with NEC [ 24 ]. One limitation of our data is that we do not have information about swab location (anal/rectal or throat) for the screening results analyzed in this study so we cannot provide information on whether certain pathogens prefer certain colonization sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organisms involved in late onset neonatal sepsis (LONS) is usually acquired from the environment rather than transmitted vertically from mother as seen in cases of early onset neonatal sepsis (EONS). 3 According to National Neonatal-Perinatal Database 2002-2003, 2219 out of 145623 (67%) neonates were found to be having EONS. 4 According to Delhi Neonatal Infection Study collaboration, total sepsis was 14.3% out of which two third cases were EONS.…”
Section: Introductionmentioning
confidence: 99%
“…Late-onset neonatal sepsis continues to cause a great deal of morbidity and mortality for very low birth weight infants (VLBW, <1,500 g BW), and earlier treatment, prior to overt clinical deterioration, could improve outcomes. 1,2 Toward this goal, researchers developed a heart rate characteristics index (HeRO score) to continuously display the risk of clinical deterioration from a sepsis-like illness in the ensuing 24-hour period, compared with the risk for all VLBW infants at all times. [3][4][5][6][7] A high HeRO score reflects the detection of abnormal heart rate patterns that might occur in sepsis: low beat-to-beat variability, increased decelerations relative to accelerations, and low sample entropy of heart rate.…”
mentioning
confidence: 99%